Microbiological and Molecular study On Candida species Isolated From Catheterized ur ine specimen In Ramadi general Teaching Hospital - Al-Obid, Waleedi Ismial Ahmid; Abaas, Zainab Khamis (AL-Kindy College Medical Journal, 2015)
Background: A Catheter-associated with candidiasis infection is the most common nosocomial infection and the objective of this work is to isolate and identify Candida species from catheterized patients by ordinary culture and PCR.Objective:To study the isolation and identification of Candida species from catheterized patients by culture media and polymerase chain reaction(PCR).Methods: One hundred and thirty five Candida species isolates were obtained from urine culture of catheterized specimens from male and female patients , During the period between October 2011 to April 2012 , attending AL-Ramadi general teaching Hospital. A quantitative urine culture for isolation and identification of Candida species was. The isolation of Candida species was done out on selective media with antibiotics is Sabouraud Dextrose Agar. The identification of Candida species was based upon a combination of morphological and biochemical criteria as germ tube test and API 20 candida. Molecular study of Candida species was done using polymerase chain reaction (PCR).Results: Out of the one hundred and thirty five catheterized urine examined .Candida spp. was isolated from in 92 samples. The isolated of Candida spp. were recorded 26(40.0%) C.albicans among female patients and 20(36.4 %) among male patients .positive candidiasis was detected among diabetic patients (28.6%) from female and (20.0%) from male .Also the candidiasis was detected among patients under antibiotic treatment was (20.3%) from female patients and (32.1%) from male patients.Polymerase chain reaction ( PCR) results showed that out of 27cultured specimens , (18) were positive for C. albicans (66.7%) , and out of 9 specimens ,(7) were positive for C.glabrata (77.8%) while out of 4specimens ,(2) were positive for C.parapsilosis (50.0%) .Statistical analysis using chi – square test was applied in this work.Conclusion: The three species of Candida. albicans , Candida .glabrata .& Candida .parapsilosis are important causes of UTI in patients under catheterization in Ramadi teaching hospital and they could be one of causes nosocomial infection .